Speech Acts in the Communication of Traditional Tongkang Burning Culture - nazhifah, nazhifah; Sumaiyah (Jurnal Paradigma, 2025)
Abstract This research aims to investigate communication in the Bakar Tongkang tradition in Bagansiapiapi, Rokan Hilir, using Speech Act Theory. The focus is directed towards the context, events, and communicative behaviour within the ritual. The research methodology employs a qualitative descriptive approach, through interviews, observations, and documentation over six months with community leaders. The results indicate that the Bakar Tongkang tradition, as a tribute to Chinese ancestors and the deity Kie Ong Ya, encompasses a series of symbolic communications, such as the construction of the tongkang, the celebration of the deity's birthday, and the burning of the tongkang symbolising new beginnings. This study highlights the context and communicative opportunities that foster cultural values and connect participants with their past. Both verbal and non-verbal communication within the ritual demonstrate respect, reinforcement of community identity, and cultural continuity. The conclusion of the research emphasizes a close relationship between speech acts, cultural identity, and collective memory. This study contributes to enriching the study of cultural communication by highlighting the role of language in the preservation of traditions. Further research is suggested to examine intergenerational communication and the role of media in maintaining the continuity of these traditions. Keywords: Burning Tongkang, Cultural Communication, Rituals, Speech Acts